Management of Renal Calculus (Mutrashmari) with Hydronephrosis by Ayurvedicformulations: A Case Study - Sonali Dilip Wairagade1 , Tanvi Wairagade2, Anuja Vasant Nagrare3 , Sandeep Iratwar4 , Gaurav Mahaja (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Stones that grow in the urinary tract (recognized as nephrolithiasis or urolithiasis) formwhen the urine becomes excessively supersaturated with respect to a mineral, leading to crystal formation,growth, aggregation and retention within the kidneys[1].Worldwide, approximately 80% of kidney stones arecomposed of calcium oxalate (CaOx) mixed with calcium phosphate (CaP). Stones composed of uric acid9%, struvite 10% and cystine of 1% are common[2].Mutrashmari (Renal calculi/Kidney stones) is one among the Ashtamahagada (eight fatal conditions) andis Kaphapradhan Tridoshaja Vyadhi. It is correlated with urolithiasis. The prevalence of symptomaticurolithiasis is approximately 10% in men and 5% in women. Many treatment modalities have been adoptedin medical sciences, but it is quite expensive and also the recurrence of development of stone cannot beavoided. Hence, it is necessary to find out easily available, an cost effective medicinetotreat Mutrashmari.Aim: To evaluate the efficacy of Shaman Chikitsa in MutrashmariMaterials and Method: It is a single case study. A 37-year-old woman who approached to outpatientdepartment of Kayachikitsa of Datta Meghe Ayurved Medical College Hospital and Research Centre withcomplaints of pain in abdomen, low backache, which was radiating from loin to groin region; burningmicturition; and dysuria. The patient was administered with Shaman Aushadhi.Results: The patient got 100% results in chief and associated complaints and during and after the completionof therapy there was an improvement in the quality of life of the patient.Conclusion: Satisfactory relief in symptoms was seen in patient after 7 days of Shaman Chikitsa.